A equipment for producing lung formula aeration sponge - Luo Guangjian; Wang Xin; Cao Xuefeng; Qin Zerong; Wang Hai; Hong Changhuai (2016)
The utility model provides an equipment for producing lung formula aeration sponge, including the pipeline body, the pipeline body sets up between storage tank and agitator tank, and storage tank and agitator tank pass through this body coupling of pipeline, and pipeline body one end is provided with the measuring pump, and pipeline body inner chamber is provided with the pivot, be provided with the filter screen in the pivot, the pipeline inner chamber is provided with rotor flow meter, pipeline body inner chamber is provided with temperature sensor, and temperature sensor is connected with the heater. Set up pivot and filter screen through intracavity in the pipeline, through the rotation of pivot, can realize opening and closing of filter function, but whether the nimble adjustment of according to actual need needs the filter screen to open. 种用于生产肺式曝气海绵的设备，包括有管道本体，管道本体设置于储料罐与搅拌罐之间，储料罐与搅拌罐通过管道本体连接，管道本体端设置有计量泵，管道本体内腔设置有转轴，所述转轴上设置有滤网；管道内腔设置有转子流量计；管道本体内腔设置有温度传感器，温度传感器连接有加热器。通过在管道内腔内设置转轴以及滤网，通过转轴的旋转，可以实现过滤网过滤功能